Assessment of the Relation between the Expression of Oxaliplatin Transporters in Colorectal Cancer and Response to FOLFOX-4 Adjuvant Chemotherapy: A Case Control Study. - Bertrand Le Roy; Lucie Tixier; Bruno Pereira; Pierre Sauvanet; Emmanuel Buc; Caroline Pétorin; Pierre Déchelotte; Denis Pezet; David Balayssac (PLoS ONE, 2016)
BACKGROUND:Adjuvant chemotherapy for colorectal cancer is mainly based on the combination of 5-fluorouracil, folinic acid and oxaliplatin (FOLFOX-4). The pharmacological target of oxaliplatin remains intracellular and therefore dependent on its entry into cells. The intracellular distribution of oxaliplatin is mediated by organic cation transporters 1, 2 and 3 (OCT1, 2 and 3), copper transporter 1 (CTR1) and ATPase Cu2+ transporting beta polypeptide (ATP7B) and may modulate the efficacy of oxaliplatin-based chemotherapy. The aim of this study was to perform a retrospective study to assess the relation between the expression of oxaliplatin transporters in colorectal cancer before chemotherapy and the response to FOLFOX-4 adjuvant chemotherapy in responder and non-responder patients. METHODS:This retrospective study was conducted at a single center (University Hospital of Clermont-Ferrand, France). The target population was patients with resectable colorectal cancer operated between 2006 and 2013. Inclusion criteria were defined for the responder patients as no cancer recurrence 3 years after the end of chemotherapy, and for the non-responder patients as cancer recurrence within 1 year. Other inclusion criteria were stages IIb-IV cancers, first-line adjuvant FOLFOX-4 chemotherapy, and the availability of resected primary tumor samples. Exclusion criteria were preoperative chemotherapy and/or radiotherapy, a targeted therapy, other anticancer drugs, cancer recurrence between the first and the third year after the end of chemotherapy and follow-up < 3 years. Immunostaining of oxaliplatin transporters (OCT1, 2, 3, CTR1 and ATP7B) and Ki-67 was assessed in tumor samples. RESULTS:Retrospectively, 31 patients have been selected according to inclusion and exclusion criteria (15 responders and 16 non-responders). Before FOLFOX-4 regimen, OCT3 expression was significantly lower in responder patients compared to non-responders (p<0.001). According to multivariate analysis, OCT3 remains an independent criterion for adjuvant FOLFOX chemotherapy response (p = 0.039). No significant relation is reported between chemotherapy response and the expression of OCT1 (p = 0.49), OCT2 (p = 0.09), CTR1 (p = 0.45), ATP7B (p = 0.94) and Ki-67 (p = 0.34) in tumors. CONCLUSIONS:High expression of OCT3 could be an independent factor related to resistance to FOLFOX-4 chemotherapy.